Towards Better Presenting and Searching of Bells Knowledge - Noev, Nikolay; Bogdanova, Galina; Todorov, Todor (Digital Presentation and Preservation of Cultural and Scientific Heritage, 2016)
The paper presents an online platform with textual data, images, audio and video recordings related to bell knowledge. It was designed to provide digital data for representation of acquired knowledge. The platform includes data repository of bell knowledge objects and a new search engine.